Развитие экспериментальной базы гидротурбостроения в ИПМАШ НАН Украины - Веремеенко, И. С.; Русанов, А. В.; Дедков, В. Н.; Агибалов, Е. С.; Гладышев, С. В. (НТУ "ХПИ", 2014)
Приведено описание основного и вспомогательного оборудования энергокавитационных стендов ЭКС-15 и ЭКС-30 лаборатории гидромашин ИПМаш НАН Украины. Показано, что гидравлические характеристики стендов и применяемых средств измерения, а также используемые процедуры градуировок первичных датчиков обеспечивают точность измерений, отвечающих требованиям кода модельных приемо-сдаточных испытаний гидротурбин и обратимых гидромашин МЭК60193.

In this article, description is given of the main and auxiliary equipment of the power & cavitation test rigs ЭКС-15 and ЭКС-30 in the hydro machinery laboratory belonging to the Institute of Mechanical Engineering Problems at Ukraine's National Academy of Sciences. It has been shown that hydraulic characteristics of the test rigs and applied measuring instruments, as well as applied calibration procedures of primary sensing elements provide for such precision of measurements that corr the requirements of the Code IEC 60 193: Model Acceptance Tests of Hydro Turbines and Reversible Hydraulic Machines.
Keywords: энергокавитационный стенд; методы измерения; погрешности измерения; процедуры градуировки